Will drones have a role in building construction? - Da Silva, N. P.; Eloy, S. (4th International Symposium Formal Methods in Architecture, 2018)
This paper aims to explore the possibilities that robotic technologies, namely robotic arms and drones, bring to architecture and to the construction sector. The developed research was based in an extensive literature review, in the conceptualization of three experiments to be done with drones and in interviews with Fabio Gramazio, Tobias Bonwetsch (ETH Zurich) and José Pedro Sousa (FAUP). The paper starts by presenting a brief story of the introduction of robotic technologies in other industries and identifies the robotic technologies that are presently use, mainly in research, to assemble construction elements – drones and robotic arms. We then analyze the few case studies of construction performed with drones and robotic arms. Three experiments are idealized next in order to clarify the main difficulties of each action of construction performed by a robot. The advances in robotic construction are visible and growing every year. According to the experts robotic construction will be introduced in the construction industry in a hybrid way, where man and machine collaborate and not as total substitution of human labor.